PENGARUH PENGENALAN GAMES ARTIFICIAL INTELLIGENCE TERHADAP PENINGKATAN KOSAKATA BAHASA INGGRIS PADA ANAK - Eksya, Sefi Apriline; Khoiriah, Alfi; Rahmatika, Wegidia Chaisa; Nurjaman, Iman; Nuary, Muhammad Guruh (Pedagogi: Jurnal Ilmiah Pendidikan, 2025)
The Effect of introducing artificial intelligence games on Increasing English vocabulary in children. This quantitative research aims to enhance lexical knowledge in young learners aged 5 to 6 Wildatun Nisa Islamic Kindergarten through artificial intelligence games monster vocab website. The subjects were 10 group B children, 5 girls and 5 boys. Methods for gathering data included observing and recording I, the average value of vocabulary improvement reached 41.3%. In cycle II, the average value increased to 63.3%. This increase shows that the introduction of the AI vocabulary animal website has a significant effect on improving English vocabulary. In addition to vocabulary improvement, this study also showed that the introduction of AI vocabulary animal website increased children's interest in learning, critical thinking skills, communication skills, along with learners’ motivation. The research shows that the introduction of AI vocabulary animal website can help children's language development and increase English vocabulary in children aged 5-6 years at Wildatun Nisa Islamic Kindergarten